Contribution of DNA methylation to the pathogenesis of Sjögren's syndrome: A review - Juliana Ramalho Guimarães; Marina de Castro Coêlho; Naila Francis Paulo de Oliveira (Taylor & Francis Group, 2022)
Sjögren's syndrome (SS) is a chronic systemic disease characterised by salivary and lacrimal gland dysfunction with severe implications for the well-being of bearing individuals. Although its origin has not yet been fully elucidated, it is known that genetic, environmental, and epigenetic factors are important contributors to the pathogenesis of this syndrome. DNA methylation is a relevant, widely studied epigenetic factor that is possibly related to the establishment of SS. The aim of the present study was to perform a systematic review of the literature to compile studies on the contribution of DNA methylation to the pathogenesis of SS. A literature search was performed in 4 databases (PubMed, Web of Science, Lilacs, and Scopus) using previously selected Medical Subject Headings (MESH) descriptors, and article selection considered observational studies only. After a full-text reading of the selected articles, 15 studies were in accordance with the eligibility criteria for data extraction. Methylation detection approaches included global methylation, genome-wide assessment of differentially methylated regions, and site-specific methylation. Fourteen articles reported associations of DNA methylation profiles in SS patients, both globally and in several genes in salivary glands and blood cells. Thus, DNA methylation may contribute to the pathogenesis of SS. The findings reinforce the importance of epigenetic markers in the dynamics of SS and may direct efforts toward the development of new diagnostic and therapeutic approaches.